Echocardiographic deformation imaging unmasks global and regional mechanical dysfunction in patients with idiopathic ventricular fibrillation: A multicenter case-control study - Groeneveld, Sanne A.; van der Ree, Martijn H.; Taha, Karim; de Bruin-Bon, Rianne H.A.; Cramer, Maarten J.; Teske, Arco J.; Bouma, Berto J.; Amin, Ahmad S.; Wilde, Arthur A.M.; Postema, Pieter G.; Hassink, Rutger J. (Heart rhythm, 2021)
Idiopathic ventricular fibrillation (IVF) is diagnosed in patients with sudden onset of ventricular fibrillation of unidentified origin. New diagnostic tools that can detect subtle abnormalities are needed to diagnose and treat patients with an underlying substrate. The purpose of this study was to explore echocardiographic deformation characteristics in IVF patients. Echocardiograms were analyzed with deformation imaging by 2-dimensional speckle tracking. Global and regional measurements of the left ventricle (LV) and right ventricle (RV) were performed. Regional LV deformation patterns were evaluated for the presence of postsystolic shortening. Regional RV deformation patterns were classified as type I (normal) or type II/III (abnormal). In total, 47 IVF patients (mean age 45 years; left ventricular ejection fraction [LVEF] 56%) and 47 healthy controls (mean age 41 years; LVEF 60%) were included. IVF patients showed more global deformation abnormalities as indicated by lower LV global longitudinal strain (18.5% ± 2.6% vs 21.6% ± 1.8%; P <.001) and higher LV mechanical dispersion (41 ± 12 ms vs 26 ± 6 ms; P <.001). In addition, IVF patients showed more regional LV postsystolic shortening compared to healthy controls (50% vs 11%; P <.001). Abnormal RV deformation patterns were observed in 16% of IVF patients and in none of the control subjects (P <.001). We were able to show both regional and global echocardiographic deformation abnormalities in IVF patients. This study provides evidence that localized myocardial disease is present in a subset of IVF patients.